Pengaruh Transfer Pricing, Intensitas Aset Tetap, dan Pertumbuhan Penjualan Terhadap Agresivitas Pajak dengan Profitabilitas sebagai Variabel Moderasi - Nabila Adri Andini; Adam Zakaria; Ati Sumiati (Teewan Journal Solutions, 2025)
This study aims to determine the effect of transfer pricing, fixed asset intensity, and sales growth on tax aggressiveness by using profitability as a moderating variable. The approach used in this research is a quantitative approach with non-primary data sources in the form of financial reports and annual reports of property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. The sampling technique in this study used purposive sampling. This research was analyzed using panel data regression with the Moderated Regression Analysis (MRA) approach. The results of this study indicate that transfer pricing and fixed asset intensity have a significant effect on tax aggressiveness. Meanwhile, sales growth has no effect on tax aggressiveness. This study also found that profitability is able to moderate the effect of transfer pricing, fixed asset intensity, and sales growth on tax aggressiveness.